ANALISIS PERSEPSI MASYRAKAT TERHADAP PERBANKAN SYARIAH (STUDI KASUS AL FIKH ORCHARD SUNGAI PINANG, MALAYSIA) - Putri Nasution, Aida Nurandini; Rahmayati, Rahmayati (Prodi Perbankan Syariah Fakultas Ekonomi dan Bisnis Islam Universitas Islam Bunga Bangsa Cirebon, 2024)
This study aims to identify how the analysis of public perception towards Islamic banking (using a case study of Al Fikh Orchard Sungai Pinang, Malaysia) affects both individually and overall. The research adopts an associative approach. The population consists of all teachers and parents at Al Fikh Orchard Sungai Pinang, Malaysia, with a sample size of 34 individuals. Data were collected through interviews, observations, and questionnaires. Data analysis was performed using Multiple Linear Regression Tests, Hypothesis Testing (t-test), and Coefficient of Determination, with the assistance of SPSS (Statistical Package for the Social Sciences) version 29.00. The analysis results indicate that the variable of public perception significantly influences public preference for Islamic banks.